The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0078928
|View full text |Cite
|
Sign up to set email alerts
|

Organization of Multisynaptic Inputs to the Dorsal and Ventral Dentate Gyrus: Retrograde Trans-Synaptic Tracing with Rabies Virus Vector in the Rat

Abstract: Behavioral, anatomical, and gene expression studies have shown functional dissociations between the dorsal and ventral hippocampus with regard to their involvement in spatial cognition, emotion, and stress. In this study we examined the difference of the multisynaptic inputs to the dorsal and ventral dentate gyrus (DG) in the rat by using retrograde trans-synaptic tracing of recombinant rabies virus vectors. Three days after the vectors were injected into the dorsal or ventral DG, monosynaptic neuronal labelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 81 publications
2
38
0
Order By: Relevance
“…Using retrograde transsynaptic viral tracers to identify first- and second-order inputs to the dorsal or ventral DG, Ohara et al (2013) recently showed that the SUM (as well as the MS and EC) was a first-order input to DG and confirmed earlier findings (Soussi et al, 2010; Vertes, 1992) that the medial SUM primarily distributes to the ventral DG and the lateral SUM to the dorsal DG. In line with the notion that the dorsal HF is primarily involved in spatial behaviors and the ventral HF in affective states (Fanselow and Dong, 2010), Ohara et al (2013) demonstrated that second-order fibers to the ventral DG (largely routed through the medial SUM) primarily originated from “affective” structures such as the ventromedial and dorsal hypothalamus, the preoptic area, and the infralimbic cortex (IL) cortex.…”
Section: Sum: Anatomysupporting
confidence: 65%
See 1 more Smart Citation
“…Using retrograde transsynaptic viral tracers to identify first- and second-order inputs to the dorsal or ventral DG, Ohara et al (2013) recently showed that the SUM (as well as the MS and EC) was a first-order input to DG and confirmed earlier findings (Soussi et al, 2010; Vertes, 1992) that the medial SUM primarily distributes to the ventral DG and the lateral SUM to the dorsal DG. In line with the notion that the dorsal HF is primarily involved in spatial behaviors and the ventral HF in affective states (Fanselow and Dong, 2010), Ohara et al (2013) demonstrated that second-order fibers to the ventral DG (largely routed through the medial SUM) primarily originated from “affective” structures such as the ventromedial and dorsal hypothalamus, the preoptic area, and the infralimbic cortex (IL) cortex.…”
Section: Sum: Anatomysupporting
confidence: 65%
“…Several reports have shown that the SUM is a major source of afferents to the hippocampus (Amaral and Cowan, 1980; Haglund et al, 1984; Harley et al, 1983; Leranth and Hajszan, 2007; Magloczky et al, 1994; Ohara et al, 2013; Soussi et al, 2010; Vertes, 1992; Vertes and McKenna, 2000; Wyss et al, 1979). For instance, Amaral and Cowan (1980) initially demonstrated that hippocampal injections of horseradish peroxidase in the monkey produced dense retrograde cell labeling in SUM—or equivalent or even greater than that seen in the septum with these injections.…”
Section: Sum: Anatomymentioning
confidence: 99%
“…Our manipulation affects both the ipsilateral and contralateral CA3-CA1 projections originating in one hemisphere; although both ipsilateral and contralateral projections do show equivalent LTP in rats (36) and mice (11), we currently cannot exclude the possibility that they play independent roles. It is also conceivable that the asymmetry in long-term memory is explained either completely or in part because the left and right CA3 receive different information, akin to how the distinct functional contributions of dorsal and ventral hippocampus might arise through differences in first-and second-order inputs (37). One possible source of asymmetry before the hippocampus might be the lateral entorhinal cortex (LEC) input to dorsal hippocampus; the left LEC exhibits a higher metabolic demand than the right LEC (38), which may be indicative of distinct computational demands present in the neuronal circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 15–18% of DA neurons in the VTA innervate the vCA1 and vSub, while only half as many DA neurons innervate dHP neurons (75, 76). Hippocampal neurons also receive emotion- and other visceral-relevant information from the amygdala, with the posterior basal medial, medial, and central regions heavily innervating the ventral and dorsal dentate gyrus (77), and the lateral amygdala innervating vSub and vCA1 (40)…”
Section: Neuroanatomical Connectivitymentioning
confidence: 99%